Managerial experience and organizational performance: a 15-year panel study of local assessors - Propheter, Geoffrey (2016)
The proposition that managerial experience improves performance is an empirical claim, yet panel studies with long time dimensions exploring the relationship are uncommon. This article investigates the impact of managerial experience on organizational performance using a 15-year panel of local property assessors in Washington State from 1999 to 2013. Each additional year of experience improves assessment quality as measured by the coefficient of dispersion by three-tenths of a percent. However, although the relationship is statistically significant, the size of the effect is quite small, with administrative practices and the environment surrounding the assessment task being stronger predictors of assessment performance. - Reproduced.
Keywords: Organizations; Managers